Symptomatic Giant Virchow-Robin Spaces: A Rare Cause of Spastic Quadriparesis in 43-Year-old Ethiopian Patient: A Case Report - Ayele, Biniyam (Ethiop J Health Sci, 2020)
BACKGROUND: Virchow-Robin Spaces (VRS) are perivascular spaces that surround small arteries and arterioles. These normal anatomical structures are thought to be involved in the drainage of interstitial fluid and also to play an immunomodulatory role by hosting macrophages. Rarely, it becomes giant and symptomatic resulting in mass effect on adjacent neuronal structures and ventricular system causing different neurological disorders. CASE PRESENTATION: We report a 43-year-old, Ethiopian woman who presented with progressive weakness of all her extremity over the period of seven years. She had associated speech difficulty, visual blurring and pseudo-bulbar affect. Neurologic examination revealed spastic quadriparesis with increased deep tendon reflexes and up going plantar bilaterally. She had horizontal nystagmus, dysarthria and reduced bilateral visual acuity, otherwise normal cognition and cranial nerves examination. Brain MRI showed T1 hypointense, T2 hyperintense and non-enhancing multiple cystic lesions of different size, mainly in bilateral basal ganglia area with mass effect on adjacent internal capsule and lateral ventricles. Considering her clinical presentation and typical radiological features, diagnosis of symptomatic dilated Virchow-Robin spaces was made, and the patient was treated symptomatically. CONCLUSION: Commonly, dilation of Virchow-Robin spaces are not symptomatic, but giant Virchow-Robin spaces, as in our patient may result in spastic quadriparesis, causing great disability on the patient. Thus, we recommend considering symptomatic Virchow-Robin spaces as a potential differential diagnosis of progressive quadriparesis, as early neurosurgical intervention may reduce the neurological complications, such as spastic quadriparesis.